Government financial management : issues and country studies - Premchand, A., 1933- (International Monetary Fund, 1990)
This book is the result of a combination of two projects. The first project was a Seminar on Budgeting and Expenditure Control organized periodically by the International Monetary Fund to meet the requirements of senior officials of its member countries. The first part of the book represents the papers contributed to the seminar that was conducted in November-December 1989 at Fund headquarters in Washington, D.C.